Neurophysiological correlates of dysregulated emotional arousal in severe traumatic brain injury. Issue 2 (February 2015) - Fisher, Alana C.; Rushby, Jacqueline A.; McDonald, Skye; Parks, Nicklas; Piguet, Olivier
Highlights EEG alpha power provides a novel index of arousal disturbances in traumatic brain injury (TBI). Diminished alpha suppression and skin conductance levels are in line with diminished arousal. Insula and amygdala volume loss may contribute to arousal dysregulation.